The Effect of Supply Chain Practices on Perceived Organizational Performance: Applied Study in Oil and Gas Industry in Egypt - Sabry, Mohamed Ahmed Ibrahim; Elwany, Hamdy; El-Nakib, Islam; Ragheb, Mohamed (International Journal of Scientific Research and Management (IJSRM), 2021)
This research focuses on to identify the relationship between supply chain management practices (supplier relationship, supply chain complexity, information sharing, information quality, logistics and strategic location) with perceived organization performance through the mediating role of supply chain performance (supply chain integration, supply chain flexibility and supplier performance) in oil and gas companies in Egypt. Then the relationship between the three variables will be tested and examined. Literature and prior studies related to this field are reviewed to construct the research hypotheses, which state that there is a significant relationship between Supply Chain Management and Supply Chain Performance, there is a significant relationship between Supply Chain Performance and Perceived Organizational Performance, and there is a significant relationship between Supply Chain Management and Perceived Organizational Performance. These hypotheses will be tested throughout the research study. Primary data is collected from supply chain employees in 61 companies of the petroleum agency in Egypt using a quantitative approach (Questionnaire). The data collected is analyzed and then the results of the analysis and findings are demonstrated by the end of the research with some recommendations to Egyptian SMEs to enhance their Perceived Organizational Performance.